A genetic toolkit for the analysis of metabolic changes in Drosophila provides new insights into metabolic responses to stress and malignant transformation. - Gándara, L.; Durrieu, L.; Behrensen, C.; Wappner, P. (Scientific reports, 2019)
Regulation of the energetic metabolism occurs fundamentally at the cellular level, so analytical strategies must aim to attain single cell resolution to fully embrace its inherent complexity. We have developed methods to utilize a toolset of metabolic FRET sensors for assessing lactate, pyruvate and 2-oxoglutarate levels of Drosophila tissues in vivo by imaging techniques. We show here how the energetic metabolism is altered by hypoxia: While some larval tissues respond to low oxygen levels by executing a metabolic switch towards lactic fermentation, the fat body and salivary glands do not alter their energetic metabolism. Analysis of tumor metabolism revealed that depending on the genetic background, some tumors undergo a lactogenic switch typical of the Warburg effect, while other tumors do not. This toolset allows for developmental and physiologic studies in genetically manipulated Drosophila individuals in vivo.